(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ensuring the integrity and confidentiality of voting processes is paramount in democratic societies. Traditional voting systems face numerous challenges, including ballot tampering, coercion, and logistical constraints. In response, cryptographic techniques have emerged as a promising solution to mitigate these vulnerabilities and enhance the security of electoral systems.